2012
DOI: 10.1111/j.1469-0691.2012.03828.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii multilocus genotyping in pooled DNA samples: a new approach for clinical and epidemiological studies

Abstract: Specific single-nucleotide polymorphisms (SNPs) are recognized as important DNA sequence variations influencing the pathogenesis of Pneumocystis jirovecii and the clinical outcome of Pneumocystis pneumonia, which is a major worldwide cause of illness among immunocompromised patients. Genotyping platforms for pooled DNA samples are promising methodologies for genetic characterization of infectious organisms. We have developed a new typing strategy for P. jirovecii, which consisted of DNA pools prepared accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…approaches has contributed significantly to our understanding of Pneumocystis biology, many questions remain unresolved (27,31). A genotyping approach with neutrally evolving markers, a high discriminatory index, and a stepwise model of allele adaptation would be a useful addition for studying P. jirovecii.…”
mentioning
confidence: 99%
“…approaches has contributed significantly to our understanding of Pneumocystis biology, many questions remain unresolved (27,31). A genotyping approach with neutrally evolving markers, a high discriminatory index, and a stepwise model of allele adaptation would be a useful addition for studying P. jirovecii.…”
mentioning
confidence: 99%
“…However, some studies on Pneumocystis genetic diversity have reported significant association between some singlenucleotide polymorphisms (SNPs) and clinical parameters in patient with PcP. Notably, SNPs at position 110 and 215 in the sod locus were described and associated with favourable outcome of PcP (SOD215C ) (Esteves et al 2010) or a lower parasite burden (SOD215C/SOD110T) (Esteves et al 2011(Esteves et al , 2012. The mitochondrial MnSOD is probably not the unique component of the Pneumocystis antioxidant system (Fig 6).…”
Section: Discussionmentioning
confidence: 99%
“…Bio-Rad, France) and nested-PCR directed to P. jirovecii large subunit mitochondrial rRNA (mtLSU rRNA) gene [12,13,33]. In the Dutch patients, P. jirovecii was detected by direct microscopy using histochemical stainings (DM/HS) (Giemsa and Grocott's methenamine silver) and real-time PCR directed to the dihydropteroate synthase (DHPS) gene of P.…”
Section: Patient Characteristics and Samplingmentioning
confidence: 99%
“…In the Spanish COPD patients, detection of P. jirovecii was performed by nested-PCR directed to the mtLSU rRNA gene [33]. [2,7,13].…”
Section: Patient Characteristics and Samplingmentioning
confidence: 99%
See 1 more Smart Citation